From Conception to Development: Investigating PROTACs Features for Improved Cell Permeability and Successful Protein Degradation - Cecchini, Carlotta; Pannilunghi, Sara; Tardy, Sébastien; Scapozza, Leonardo (Frontiers in Chemistry, 2021)
Proteolysis Targeting Chimeras (PROTACs) are heterobifunctional degraders that specifically eliminate targeted proteins by hijacking the ubiquitin-proteasome system (UPS). This modality has emerged as an orthogonal approach to the use of small-molecule inhibitors for knocking down classic targets and disease-related proteins classified, until now, as “undruggable”. In early 2019, the first targeted protein degraders reached the clinic, drawing attention to PROTACs as one of the most appealing technology in the drug discovery landscape. Despite these promising results, PROTACs are often affected by poor cellular permeability due to their high molecular weight (MW) and large exposed polar surface area (PSA). Herein, we report a comprehensive record of PROTAC design, pharmacology and thermodynamic challenges and solutions, as well as some of the available strategies to enhance cellular uptake, including suggestions of promising biological tools for the in vitro evaluation of PROTACs permeability towards successful protein degradation.